Descriptive study of clinical profile and outcome in patients of acute on chronic liver failure, at a tertiary care center in Northern India - Kumar, Rakesh; Rana, Vandana; Koshy, Varghese; Gangadharan, Vandana; Koshy, George (International Journal of Advances in Medicine, 2020)
Background: Acute-on-chronic liver failure (ACLF) is a recently described syndrome that is characterized by abrupt deterioration in patients with chronic liver disease (CLD) and has high short-term mortality. The aim of this study was to describe the clinical profile, causes and outcomes of ACLF at a tertiary care centre in Northern India. Methods: In this descriptive study of 50 consecutive patients, were included, between August 2015 to January 2018, who were admitted and diagnosed as ACLF as defined by APASL. Causes of acute precipitating event and CLD and outcomes were assessed. Occurrence and severity of organ failure was also assessed. Results: 48 (96 %) were males and 2 (4%) were females with male to female ratio was 24:1. The mean age of male and female subjects was similar, 40.7±9.9 years and 39.2±9.4 years respectively. The most common cause of CLD was alcohol in 50% cases and next most common cause was hepato-tropic viruses HBV infection in 20%, HCV in 6% cases and there was unknown cause in 12 % cases. The most common precipitating factor of acute decompensation was alcohol in 50% cases, hepatotropic viruses in 30% cases. Excluded sepsis and GI bleed as precipitating events. The combined mortality at the end of 1-month and 3-months, in our study was 60%. CLIF-SOFA score was found to be the most reliable scoring system to discriminate between survivors and non survivors. Conclusions: Alcohol was the commonest precipitating cause of ACLF. Organ failures (OFs) are independently predictive of mortality.